2023
DOI: 10.3390/microorganisms11030560
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre Surveillance of Candida Species from Blood Cultures during the SARS-CoV-2 Pandemic in Southern Europe (CANCoVEU Project)

Abstract: Introduction: Surveillance of Candida species isolates from blood cultures (BCs) in Europe is considered fragmented, unable to allow the definition of targets of antifungal stewardship recommendations especially during the SARS-CoV-2 pandemic. Methods: We performed a multicentric retrospective study including all consecutive BC Candida isolates from six Southern European tertiary hospitals (1st January 2020 to 31st December 2021). Etiology, antifungal susceptibility patterns, and clinical setting were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…To the authors’ knowledge, this is the first Portuguese multicenter observational and descriptive study that provides insights into Candida colonization and predictive risk factors in an ICU setting. Previous studies conducted in Portugal have predominantly focused on cases of candidemia, often being retrospective in nature [ 25 , 26 , 27 ]. Nevertheless, comparing the overall distribution of Candida species with previous Portuguese candidemia studies, a steady pattern of Candida species ranks yielded by Portuguese ICU patients was observed [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the authors’ knowledge, this is the first Portuguese multicenter observational and descriptive study that provides insights into Candida colonization and predictive risk factors in an ICU setting. Previous studies conducted in Portugal have predominantly focused on cases of candidemia, often being retrospective in nature [ 25 , 26 , 27 ]. Nevertheless, comparing the overall distribution of Candida species with previous Portuguese candidemia studies, a steady pattern of Candida species ranks yielded by Portuguese ICU patients was observed [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, comparing the overall distribution of Candida species with previous Portuguese candidemia studies, a steady pattern of Candida species ranks yielded by Portuguese ICU patients was observed [ 28 ]. Namely, a prevalence of C. albicans alongside the occurrence of cryptic species only from the C. parapsilosis complex [ 26 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients hospitalized with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, the virus that causes COVID-19, are at increased risk for secondary infections with Candida spp., which can be severe and life-threatening. [1][2][3][4] Prior studies identified risk factors for healthcare-associated candidiasis in patients hospitalized with COVID-19, including age, length of intensive care unit (ICU) stay, comorbidities, central venous catheters, mechanical ventilation, extracorporeal membrane oxygenation (ECMO), antibiotic exposure, and Candida colonization. [5][6][7] It remains unclear if there are any risk factors for candidiasis that are unique to patients with COVID-19, including use of immunosuppressive medications such as corticosteroids and interleukin-6 (IL-6) inhibitors.…”
Section: Introductionmentioning
confidence: 99%